2017
DOI: 10.5603/ep.a2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine profile in patients with anorexia nervosa

Abstract: Introduction: Anorexia nervosa (AN) is an eating disorder characterised with extremely low weight. Adipokines are adipose tissuederived substances that show a wide spectrum of biological activities. We aimed to assess selected adipokine levels in women with AN before and after nutritional intervention. We also sought to examine whether BMI is the only confounding factor influencing adipokine assessment in AN. Material and methods: Sixty-five women participated in the study: 20 individuals with AN before any tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…However, there was no decrease of adiponectin dependent on increasing BMI in LSS patients as would have been predicted by this model. This finding is in line with a recent study that reported no difference in adiponectin levels between treatment naïve AN patients (mean BMI 15.6 ± 1.1 kg/m 2 ) and a group of re-fed AN patients [ 28 ]. A possible explanation may be given by the fact that the increase in BMI was considerably lower in LSS patients compared to HSS patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no decrease of adiponectin dependent on increasing BMI in LSS patients as would have been predicted by this model. This finding is in line with a recent study that reported no difference in adiponectin levels between treatment naïve AN patients (mean BMI 15.6 ± 1.1 kg/m 2 ) and a group of re-fed AN patients [ 28 ]. A possible explanation may be given by the fact that the increase in BMI was considerably lower in LSS patients compared to HSS patients.…”
Section: Discussionsupporting
confidence: 92%
“…The dysregulation of adipokine synthesis can alter homeostasis and lead to pathological conditions [ 8 ]. The majority of research has focused on obesity and its impact on the adipokine profile, although a few papers consider the adipokine pattern in an undernutrition state, such as anorexia nervosa [ 42 , 43 ]. Analyzing adipokine status, Mantovani et al [ 44 ] suggested that leptin, resistin, or adiponectin might be early markers of changing from lean to obesity, even before the occurrence of metabolic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that there are over 50 different adipokines secreted from adipose tissue [48][49][50][51]. The main processes regulated by adipokines may be divided into three groups: 1. lipids and glucose metabolism; 2. inflammatory processes; and 3. blood pressure and haemostasis.…”
Section: Hormonal Activity Of Adipose Tissuesmentioning
confidence: 99%